Nutrition for Health and Fitness: Fat in Your Diet - Linda B. Bobroff (EDIS)
We frequently hear about the epidemic of obesity. We also hear a variety of recommendations for how much and what type of fat we should have in our diets. With new research being published all the time, it can get confusing for consumers. This 8-page fact sheet is a major revision that provides tips to help individuals meet dietary guidelines and reduce health risks, as well as a few tasty recipes to try. Written by Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, revised March 2017.